2020
DOI: 10.1038/s41388-020-01576-6
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell carcinoma-derived exosome-shuttle miR-375 induces fibroblast polarization by inhibition of RBPJ and p53

Abstract: Merkel cell carcinoma (MCC) is a highly invasive and metastatic skin cancer. While high expression of miR-375 is a characteristic of MCC, it seems not to contribute to the malignant phenotype of MCC cells. miR-375 enrichment in MCC-derived extracellular vesicles suggests its intercellular signaling function. Here, we demonstrate that horizontally transferred miR-375 causes fibroblast polarization toward cancer-associated fibroblasts (CAFs). The polarization is evidenced by phenotypic changes and induction of α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…Given that very few studies have thoroughly addressed the biological significance of stromal cells in MCC progression, our investigation is the first to provide evidence that these cells may play a relevant role in modulating tumor growth, particularly angiogenesis. This new paradigm would be consistent with a recent report showing that intercellular communication between MCC cells and stromal fibroblasts is required for the generation of activated/polarized CAFs (Fan et al ., 2021). Consistent with our findings, variability/heterogeneity of stromal components populating MCC lesions has been reported, a phenomenon also observed in many other cancers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Given that very few studies have thoroughly addressed the biological significance of stromal cells in MCC progression, our investigation is the first to provide evidence that these cells may play a relevant role in modulating tumor growth, particularly angiogenesis. This new paradigm would be consistent with a recent report showing that intercellular communication between MCC cells and stromal fibroblasts is required for the generation of activated/polarized CAFs (Fan et al ., 2021). Consistent with our findings, variability/heterogeneity of stromal components populating MCC lesions has been reported, a phenomenon also observed in many other cancers.…”
Section: Discussionsupporting
confidence: 92%
“…A more recent study provided evidence of exosome transmitted cargo on the TME in MCC. Exosome transmitted miRNA-375 induced activation of αSMA-1, CXCL2, and IL- 1β genes, suggesting that horizontally transferred miR-375 is critical for polarizing fibroblasts toward a CAF phenotype in MCC (Fan et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Becker and his group showed that extracellular vesicle-mediated transmission of miR-375 to fibroblasts caused phenotypic changes toward cancer-associated fibroblasts. This observation suggests that miR-375 may contribute to generating a tumor microenvironment [ 276 ].…”
Section: Oncoviruses and Micrornamentioning
confidence: 99%
“…The self-renewal medium was further supplemented with chicken embryo extract containing HBSS, PBS (PAN Biotech), MEM with Earle's salts and L-glutamine (Thermo Fischer) and Hyaluronidase specs (Sigma Aldrich) [42]. Primary cutaneous fibroblasts (F 1.15) were generated and maintained as previously described [43].…”
Section: Cell Lines and Tissuesmentioning
confidence: 99%